Comparison of the mean healing time of wound after vacuum assisted closure versus conventional dressing in diabetic foot ulcer patients - Mooghal, Mehwish; Usman, Muhammad; Khan, Wajiha; Brohi, Lal Bux; Ahmad, Asrar; Rahim, Kamran (International Journal of Clinical Trials, 2021)
Background: Diabetic foot ulcers (DFU’s) are chronic wounds in diabetics resulting from ischemia, angiogenesis defects and impaired immunity. Vacuum assisted closure (VAC) provides a new paradigm for diabetic wound dressing. This study compares the mean healing time of wound after VAC versus conventional dressing (CD) in DFU patients. Methods: This randomized controlled trial carried out at surgery department, at tertiary teaching hospital over a period from 28th February-27th August 2020. Total 60 patients of age (25-75 years), both genders having DFU were included. Patients were placed randomly into two groups i.e., group A (VAC therapy) and group B (CD), by using lottery method. Mean healing time noted in both groups. For statistical analysis, SPSS version 20.0 was used. Independent ‘t’ test used to compare the mean healing time of both groups and p≤0.05 considered significant. Effect modifiers were controlled through stratification and post-stratification independent ‘t’ test, to see their effect on healing time. P≤0.05 was considered significant. Results: The mean age of patients in group A was 53.13±9.09 years and in group B was 53.53±9.09 years. Out of 60 patients 41 (68.33%) were males and 19 (31.67%) were females. The mean healing time of wound in DFU patients after VAC closure (group A) was 12.07±2.15 days and after CD (group B) was 17.50±3.16 days with p=0.0001. Conclusions: Study concluded that mean healing time after VAC is less in DFU patients as compared to CD.